Commutative regulation between endothelial NO synthase and insulin receptor substrate 2 by microRNAs. (8th October 2018) - Sun, Xiaoli; Lv, Huizhen; Zhao, Peng; He, Jinlong; Cui, Qinghua; Wei, Minxin; Feng, Shiqing; Zhu, Yi
Abstract: Endothelial NO synthase (eNOS) expression is regulated by a number of transcriptional and post-transcriptional mechanisms, but the effects of competing endogenous RNAs (ceRNAs) on eNOS mRNA and the underlying mechanisms are still unknown. Our bioinformatic analysis revealed three highly expressed eNOS-targeting miRNAs (miR-15b, miR-16, and miR-30b) in human endothelial cells (ECs). Among the 1103 mRNA targets of these three miRNAs, 15 mRNAs share a common disease association with eNOS. Gene expression and correlation analysis in patients with cardiovascular diseases identified insulin receptor substrate 2 (IRS2) as the most correlated eNOS-ceRNA. The expression levels of eNOS and IRS2 were coincidentally increased by application of laminar shear but reduced with eNOS or IRS2 siRNA transfection in human ECs, which was impeded by Dicer siRNA treatment. Moreover, luciferase reporter assay showed that these three miRNAs directly target the 3′UTR of eNOS and IRS2. Overexpression of these three miRNAs decreased, whereas inhibition of them increased, both mRNA and protein levels of eNOS and IRS2. Functionally, silencing eNOS suppressed the Akt signal pathway, while IRS2 knockdown reduced NO production in ECs. Thus, we identified eNOS and IRS2 as ceRNAs and revealed a novel mechanism explaining the coincidence of metabolic and cardiovascular diseases.